Construção e utilização de secadores solares para avaliação de desempenho na desidratação de frutas tropicais - Dantas, Alessandra Raquel (Universidade Federal Rural do Semi-Árido, 2019)
Nowadays, the progress of countries is increasingly linked to sustainable development. Brazil is the third largest producer of fruit in the world. In this way, solar drying of fruits is a renewable technology that aims to promote a better conservation of fruits, by means of the elimination of water, allowing them to be stored for an extended period of time. Solar drying adds value, reduces weight, and facilitates its transport to other regions. The work has as general objective, the construction of two solar driers direct exposure, simple and low cost, being one of wood and another of styrofoam, for the accomplishment of a study of the efficiency and obtaining the curves of drying of the guava, pineapple and mango. The fruits were dehydrated in both dryers, in order to compare the curves obtained in the two equipments. The samples were weighed every 10 minutes and the drying air temperatures were monitored in real time, with the aid of a digital multimeter that transmitted the data to the computer. Solar dryers are suitable for our Northeast region, and may emerge as a new source of income for the local population. The Styrofoam solar dryer showed a higher efficiency at the end of the process, with water evaporation rates higher than that of wood, even with a drying time of less than 70 minutes. Because it is a dryer that has promoted better thermal insulation, the lower the heat losses to the environment.
Artigo
Keywords: Secagem solar; Frutas tropicais; Curvas de secagem; Solar drying; Tropical fruits; Drying curves; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA